Pembangunan Sistem Chatbot Informasi Objek Wisata Kota Malang berbasis Web - Rizkey Wijayanto; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Malang City is one of the cities in East Java Province in Indonesia which has a lot of potential to be used as a tourist destination that can be visited by both domestic and foreign tourists. Data shows that the number of tourists visiting Malang is less than that of Batu City. The small number of tourists is caused by several factors. One of them is the lack of information related to tourist attractions in the city of Malang. To deal with these problems, a system development that aims to make it easier for tourists to get information about Malang city tourist destinations. In addition to finding information the system can also be used by tourists to submit proposed tourism locations that may not have been registered. Tourists can also provide value to tourist sites so that they can be used as a reference for tourism managers in building good tourism locations. The system was built using the Laravel framework which has more features than other frameworks and uses BotMan for the construction of chatbots in order to provide interactive information and with map support for more accurate location indicators. Testing is done by testing three aspects, namely unit testing, integration testing and validation testing in which all three tests produce a value of 100% valid. In compatibility testing we get the results that the system can run on 8 types of browsers. It is expected that this development will make it easier for tourists to access and obtain information about Malang City tourism.